LES FACTEURS ASSOCIES A LA SURVENUE DE LA MACROSOMIE CHEZ LE NOUVEAU-NE A Lâ€™HOPITAL REGIONAL CHERIF IDRISSI DANS LA REGION DU GHARB MAROC - EL Bakkali, Mohamed; Azzouzi, Younes; Khadmaoui, Abderrazzak; Thami Ahami, Ahmed Omar; EL Khlifi, Farid (European Scientific Journal, ESJ, 2014)
The objective of this study was to identify risk factors associated with the occurrence of macrosomia in newborns from 327 deliveries at the Maternity Hospital Regional Sharif Idrissi in the Gharb region Morocco. Retrospective analytical study on macrosomia carried out Regional Hospital Sharif Idrissi in the Gharb region from 01/04/2011 to 30/09/2011 period. we analyzed the factors associated with macrosomia and used as a statistical test :Yule ’s Q Test and chi-square for univariate analysis of risk indicators and liaison between an exposure factor and macrosomia and multivariate by multiple regression to quantify the relation between the dependent and independent variables, with a threshold of less than or equal to 5 % significance . This study involved a total of 327 newborns, with an incidence of 14,37% macrosomic. Weight newborns ranged between 1100 and 5000 g. We kept initially in univariate analysis as risk factors : 55.5% (p <0,001) of cases with a BMI greater than 30, multiparity between 20,5 and 21,1 % (p < 0.01), the gestational age that exceeds 40 SA 25.0 % (p < 0,02) , the higher interval inter gestational or equal to 5 years of 25,0 % ( p < 0.01 ),childbirth cup 44% (p <0,001), employment history instrument 24,5% (p <0,05)and 20,0% non followed pregnancy ( p < 0,02 ) . In multivariate analysis adjusted for other variables, the factors most strongly associated with the occurrence of macrosomia (positive relationship) are: BMI greater than 30 ( Ïƒ = 0,470 , Î² = 0,212 , p â‰¤ 0,001) , multiparity ( Ïƒ = 0, 750 , Î² = 0,182 , p â‰¤ 0.001) and gestational age greater than 40 weeks of amenorrhea (SA), (Ïƒ = 0,470, Î² = 0,212, p = 0.014).The macrosomia is often the cause of fetal and maternal complications. Its management must be multidisciplinary.